Piloting a clinical laboratory method to evaluate the influence of potential modified risk tobacco products on smokers' quit-related motivation, choice, and behavior. (December 2019) - Ozga-Hess, Jenny E.; Felicione, Nicholas J.; Ferguson, Stuart G.; Dino, Geri; Elswick, Daniel; Whitworth, Catherine; Turiano, Nicholas; Blank, Melissa D.
Abstract: Research methods are needed that can predict whether the availability of potential modified risk tobacco products (MRTPs) may influence smokers' quit-related motivation, choice, and behavior. This pilot study assessed the primary outcomes of feasibility and adherence to address this need using an electronic cigarette (ECIG) as a model MRTP. Cigarette smokers were randomly assigned to use only their own brand of cigarettes (OB-only) or a second-generation ECIG (18 ng/ml nicotine) plus their OB cigarettes (ECIG+OB) ad libitum for four weeks. Participants logged products using a mobile device, collected used cigarette filters, and provided saliva samples every day for analysis of cotinine. They returned to the lab once per week to provide a breath sample and accept or decline a choice to quit all tobacco products (i.e., cigarettes and/or ECIGs). They also returned for a one-month follow-up visit. Of those participants randomized ( n = 60), 56.7% completed the 4-week intervention and 40.0% completed the follow-up visit. The primary reason for withdrawal was poor adherence with mobile device use. Comparable numbers of participants in each group chose to make a quit attempt, although more OB-only participants chose to quit during the first two weeks and more ECIG+OB participants during the last two weeks. With protocol modifications to reduce participation burden, the current method might ultimately be used by regulators to predict how smokers' quit-related motivation, choice, and behavior are influenced by current and future MRTPs. Highlights: Method to evaluate how MRTPs influence quit motivation, choice, and behavior. ECIG availability may delay quit attempts. ECIG availability may not impact cessation outcomes. Results need to be replicated with larger sample sizes and a range of devices.